Effects of Elbow Crutch Locomotion on Gluteus Medius Activation During Stair Ascending - De la Fuente, Carlos; Neira, Alejandro; Torres, Gustavo; Silvestre, Rony; Roby, Matias; Yañez, Roberto; Herrera, Sofia; Martabit, Virgina; McKay, Isabel; Carpes, Felipe P. (Frontiers in Bioengineering and Biotechnology, 2022)
Crutches can help with the locomotion of people with walking disorders or functional limitations. However, little is known about hip muscle activation during stair ascending using different crutch locomotion patterns in people without disorders and limitations. Thus, we determined the acute effects of elbow crutch locomotion on gluteus medius (GM) activity during stair ascending. This comparative analytic cross-sectional study enrolled ten healthy men (22.0 ± 0.47 years). Participants climbed up the stairs with elbow crutches using one or two crutches, with ipsilateral or contralateral use, and after loading or unloading a limb. EMG signals were recorded from anterior, middle, and posterior portions of the GM and compared between the crutch conditions. The Kruskal–Wallis test and Dunn’s multiple comparison test were performed (α = 5%). The activation of the GM increased with the ipsilateral use of crutches, with two crutches and three points, and when all the load depended only on one limb. GM activation decreased with contralateral use and in the unload limb. In conclusion, ascending stairs with elbow crutches alters the GM activation. The more critical factors were choosing the crutches’ lateral use, the number of crutches, and if the limb is loaded or unloaded while ascending the stairs. Our findings can be helpful to increase or decrease the GM activation for those who use or will use crutches.